1997
DOI: 10.1021/bi963044m
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Endonuclease Activity of Phage λ Terminase:  Assembly of a Catalytically Competent Nicking Complex Is Rate-Limiting

Abstract: The terminase enzyme from bacteriophage lambda is responsible for excision of a single genome from a concatameric DNA precursor and its insertion into an empty viral procapsid. The enzyme possesses a site-specific endonuclease activity which is responsible for excision of the viral genome and the formation of the 12 base-pair single-stranded "sticky" ends of mature lambda DNA. We have previously reported a kinetic analysis of the endonuclease activity of lambda terminase which showed an enzyme concentration-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 36 publications
6
54
0
Order By: Relevance
“…Studies on the ATPase activity of the isolated terminase subunits have similarly revealed that the isolated gpNu1 subunit possesses weak ATPase activity while gpA efficiently hydrolyzes ATP (17,34,40). Consistently, the isolated hexa-His gpNu1 subunit possesses modest ATP hydrolysis activity, whereas hexa-His gpA hydrolyzes ATP at a rate similar to that of the wild-type subunit (Table V).…”
Section: Catalytic Activity Of the Isolated Wild-type And Hexa-histagmentioning
confidence: 72%
See 3 more Smart Citations
“…Studies on the ATPase activity of the isolated terminase subunits have similarly revealed that the isolated gpNu1 subunit possesses weak ATPase activity while gpA efficiently hydrolyzes ATP (17,34,40). Consistently, the isolated hexa-His gpNu1 subunit possesses modest ATP hydrolysis activity, whereas hexa-His gpA hydrolyzes ATP at a rate similar to that of the wild-type subunit (Table V).…”
Section: Catalytic Activity Of the Isolated Wild-type And Hexa-histagmentioning
confidence: 72%
“…The lysates were treated with chloroform, clarified, and plated for phage yield on the IHF ϩ strain MF1427. Terminase Activity Assays-The cos cleavage assay was performed as described previously using pAFP1 as a nuclease substrate (6,34). ATPase catalytic activity was examined as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed rate of cos-cleavage is stimulated by ATP, ADP, and GDP, but interestingly, not GTP [22,29,59,85,106]. IHF also stimulates the observed rate two-to threefold, but only when the terminase concentration is limiting [23,85,107]. The reaction kinetics are characterized by a single enzymatic turnover and the data suggest that two terminase protomers are required to efficiently nick the duplex [23,107].…”
Section: Endonuclease (Cos-cleavage) Activitymentioning
confidence: 92%